Tf2NH-catalyzed 1,6-conjugate addition of vinyl azides with p-quinone methides: a mild and efficient method for the synthesis of β-bis-arylamides - Rathod, Jayant; Sharma, Brijesh M.; Mali, Pramod S.; Kumar, Pradeep (Synthesis, 2017)
Tf2NH-catalyzed tandem 1,6-conjugate addition/Schmidt type rearrangement using vinyl azides and p-quinone methides to access a variety of β-bis-arylated amides is reported. The method is quick, efficient, mild, and high yielding with broad substrate scope.

Tf2NH catalyzed 1,6-conjugate addition of 2-hydroxy-p-quinone methides with -functionalized ketones: access to 2,3,4,9-Tetrahydro-1H-xanthenones and 4H-Chromene Derivatives - Satbhaiya, Shruti; Khonde, Nilesh S.; Rathod, Jayant; Gonnade, Rajesh; Kumar, Pradeep (European Journal of Organic Chemistry, 2019)
A Bronsted acid catalyzed tandem 1,6-conjugate sequential cycloaddition reaction using 2-hydroxy-p-quinone methides and -functionalized ketones is reported. The method allows xanthenones and chromenes to be accessed in moderate to excellent yield with broad substrate scope, which could be further functionalized to give a versatile set of products.
Keywords: -Functionalized ketone; 1; 6-Conjugated addition; Bronsted acid; Chromenes; Xanthenones